Prototype Measuring Levels of Dissolved Ammonia Based on TSL2561 Sensor Calibrated Thermo Scientific Genesys 30 Visible Spectrophotometer - Titin Putri Aripta; Sri Wahyu Suciyati; Amir Supriyanto; Junaidi Junaidi (Journal of Energy, Material, and Instrumentation Technology, 2022)
In this study, a prototype measuring instrument for dissolved ammonia levels based on the TSL2561 sensor and calibrated thermo scientific Genesys 30 visible spectrophotometers has been realized, which aims to create a system for reading dissolved ammonia levels. This measuring instrument uses a violet LED as a light source, Arduino UNO as the central processor, and an I2C LCD to display measured values. This research was carried out by reading sensor tests on artificial instruments and spectrophotometer with dissolved ammonia samples with levels varying from 0-0.3 mg/l to obtain an equation for converting the absorbance value of the artificial measuring instrument into the dissolved ammonia level value, which was implemented in the Arduino program. Furthermore, an artificial measuring instrument is applied by measuring the dissolved ammonia level in the wastewater sample, namely the wastewater from the shrimp seeds tank, artemia tank, and tilapia tank. This measuring instrument has a measurement range from 0-0.3 mg/l. The sensor test results show that the greater the dissolved ammonia level, the greater the absorbance value. The results of the application of artificial measuring instruments obtained the value of dissolved ammonia levels in the wastewater of the shrimp seeds tank of 0.2811 mg/l, the wastewater of the artemia tank of 0.0672 mg/l, and the wastewater of the tilapia pond at 0.0156 mg/l. Based on the calculation results, it was obtained that the average accuracy and precision for the shrimp seeds tank wastewater was 98.63% and 98.47%, the Artemia tank wastewater was 97.72% and 98.08%, while for the pond wastewater tilapia by 95.71% and 99.74 %.